2013
DOI: 10.1124/dmd.112.048884
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins-12 and -23 Do Not Alter Expression or Activity of Multiple Cytochrome P450 Enzymes in Cryopreserved Human Hepatocytes

Abstract: Psoriasis is a T-cell-mediated autoimmune disease involving the skin. Two cytokines, interleukin-12 (IL-12) and IL-23 have been shown to play a pivotal role in the pathogenesis of the disease. Ustekinumab (Stelara) is a therapeutic monoclonal antibody (mAb) targeted against the p40 shared subunit of . Recently the ability of therapeutic proteins (TP) including mAbs that target either cytokines directly (e.g., Pegasys; peginterferon a-2a) or their respective cell surface receptors [e.g., tocilizumab (Actemra); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Interleukin‐6 has been shown to modulate multiple CYP enzyme activities in in vitro models using cultured human hepatocytes . Previous research reported that 10 ng/ml IL‐6 suppressed the activity and/or mRNA expression of CYP3A, CYP2C9, CYP2C19, or CYP2B6 by >45% . The present study investigated the effects of sirukumab on CYP enzyme activities in a clinical setting using a cocktail DDI approach.…”
Section: Discussionmentioning
confidence: 96%
“…Interleukin‐6 has been shown to modulate multiple CYP enzyme activities in in vitro models using cultured human hepatocytes . Previous research reported that 10 ng/ml IL‐6 suppressed the activity and/or mRNA expression of CYP3A, CYP2C9, CYP2C19, or CYP2B6 by >45% . The present study investigated the effects of sirukumab on CYP enzyme activities in a clinical setting using a cocktail DDI approach.…”
Section: Discussionmentioning
confidence: 96%
“…When studied for an effect on CYP3A4, IL-6 also appears to be more potent than IL-1 in this respect (Dickmann et al, 2012). In contrast to IL-1 and IL-6, others such as IL-12 and IL-23 have been shown not to alter the expression or activity of cytochrome P450 enzymes (Dallas et al, 2013). Similarly, administration of IL-10 to healthy volunteers did not alter CYP1A2, CYP2C9, or CYP2D6 activities but it did reduce CYP3A activity, as measured by use of probe drugs caffeine (CYP1A2), tolbutamide (CYP2C9), dextromethorphan (CYP2D6 and CYP3A), and midazolam (CYP3A) (Gorski et al, 2000).…”
Section: Downloaded Frommentioning
confidence: 98%
“…In this case, a sufficient understanding of the cytokines in question (i.e., the absence of IL-12 and IL-23 receptors in hepatocytes) was available. However, the implications of these factors with respect to TP-DDI risk had not been generally established, therefore in vitro studies were conducted and supported the hypothesis that IL-12 or IL-23 would not directly suppress cytochrome P450 enzymes (Dallas et al, 2013a). Similar studies on diverse cytokines (both pro-and anti-inflammatory) and disease indications will help to elucidate molecular pathways that are affected and determine which cytochrome P450 isoforms may be suppressed.…”
Section: The Tp-ddi Workhopmentioning
confidence: 98%